Pengembangan Media Pembelajaran Sicabox Materi Sifat-Sifat Cahaya untuk Meningkatkan Kemampuan Berpikir Ilmiah Siswa - Syaipul, Ahmad; Yusuf, Raudhatun Nisa; Munte, Sartika Sari; A. Hrp, Widiya Anggraeny (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Scientific thinking is a process that combines induction and deduction. Induction, namely drawing specific statements to make general conclusions, while deduction draws general statements to make special conclusions. The research method used in this study is the research and development method, or better known as development research. According to Sukmadinata Research and Development is a research approach to produce a new product or improve an existing product. This means that with the help of a tool in the form of SICABOX media, it makes students understand more about the material properties of light. Not only that, the existence of tools such as SICABOX media can help the effectiveness and efficiency of learning to take place. Because with SICABOX media, students become enthusiastic and more enthusiastic about learning. Keywords: sicabox media, light properties, scientific thinking